COTIDIANO E CONFLITO DE INDÍGENAS NOS CAMPOS DE TIBAGI E GUARAPUAVA (1855-1885) - Meira, Ana Paula Galvão de (2015)
The historical remains of human groups interfere in the understanding and analysis of these, by the researchers. In relation to the Brazilian Indians, production on them always at the discretion of a party therefore did not depend on a written culture to orient themselves in their ancient practices. The orality was the means of access to the necessary information and the insertion process in groups according to their traditions. Analyze the intervention of a human group through only documents produced by an outside agency, is challenging. Documents produced from the nineteenth century occasionally influenced the transformation of ethnohistory. The government`s concern with the `problem` of savages, that prevented the migratory expansion of national progress, collaborated in the range of reports, crafts, regulations and laws that currently allows us to visualize the Indian acting in historical context. Filter derogatory and seek discuss indigenous resistance of practical information has been one of the alternatives of historians. Was one of the main objectives in this paper, we try to insert it in the historical process of Indian historiographical construction. Through the daily life of principle established by Michel de Certeau, is aimed to reflect on the tactics of the natives, from the analysis of crimes recorded in the regions of Tibagi and Guarapuava fields, between 1855-1885, involving such agents.